FACTORS INFLUENCING DECISION-MAKING ON THE OUTCOME OF UNINTENDED PREGNANCY AMONG MARRIED WOMEN IN IBADAN SOUTH-WEST LOCAL GOVERNMENT AREA, NIGERIA (2014)
Unintended pregnancy is a potential risk for women which could adversely affect their health, family and society at large. In Nigeria, information on factors influencing decision-making on unintended pregnancy among married women has not been adequately explored. This study was designed to assess the factors that influence decision making on unintended pregnancy among married women in Ibadan South-West Local Government Area (IBSWLGA), Nigeria. This study was exploratory and involved the use of qualitative methods. The study is also phenomenological in design. Ten out of the 12 wards in the LGA were selected through balloting for Focus Group Discussions (FGDs) while the remaining two were used for In-depth Interviews (IDIs). One community each was randomly selected from each ward for the FGDs. Ten FGDs were conducted among purposively selected women of child-bearing age who have had two children in the past five years. Four IDIs (2 per ward) were conducted among women who had had unintended pregnancy. FGD guide and IDI schedule containing questions on decision-making, spouses’ reaction, induced abortion and use of contraceptives were used to collect data. Responses were transcribed and analysed thematically. Participants’ ages ranged from 19-49 years with a mean age of 30.0 ± 5.63. Majority (81.0%) were Yorubas with 53.6% being Muslims. Those who had secondary education (60.7%) were in the majority, while traders constituted 61.9%. A large proportion (71.2%) had been married for 5-20 years. Many of the FGD discussants had experienced unintended pregnancies during the nursing period of a previous child. Factors identified as influencing the decision to carry unintended pregnancy to term included: spousal support, fear of complications, unsuccessful induced abortion and desire to have more children. Decision to terminate pregnancy was influenced by lack of spousal support, economic implication of caring for another child, fulfilment of the number of children desired with preferred sexes and pregnancy complications. One out of the four IDI participants terminated the pregnancy before term. Majority reported misunderstanding between them and their spouses as a result of unintended pregnancy. Majority stated that they and some of their neighbours who experienced unintended pregnancy visited health centres for antenatal care. The IDI participants were against the procurement of abortion while majority of the FGD discussants indicated that abortion procurement was common in marriage. Majority were aware of the different types of contraceptives and their effectiveness in the prevention of unintended pregnancy but did not use any for fear of side effects. Unintended pregnancy and non-utilisation of contraceptives were common among the participants. Intervention focusing on the couple as a unit should be instituted to improve spousal communication and uptake of family planning products thereby reducing the occurrence of unintended pregnancy.